2006
DOI: 10.1021/es051228v
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Thermal and Optical Measurement Methods for Elemental Carbon and Black Carbon at an Urban Location

Abstract: Despite intensive efforts during the past 20 years, no generally accepted standard method exists to measure black carbon (BC) or elemental carbon (EC). Data on BC and EC concentrations are method specific and can differ widely (e.g. Schmid et al., 2001, ten Brink et al., 2004). In this study, a comprehensive set of methods (both optical and thermal) is compared. Measurements were performed under urban background conditions in Vienna, Austria, a city heavily impacted by diesel emissions. Filter and impactor sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 37 publications
7
97
0
1
Order By: Relevance
“…The aerosol absorption coefficient values obtained at Granada in summer (5-28 Mm −1 ) are similar to those obtained by a MAAP (the same instrument used in this study) during summer 2002 in Vienna (population 1.8 million) which ranged from 8-30 Mm −1 (Hitzenberger et al, 2006). In addition, the mean value of σ ap (21±10 Mm −1 ) observed at Granada is also comparable to the values of σ ap of 22 Mm −1 obtained at the urban costal Toulon, France during (Saha et al, 2008.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbesupporting
confidence: 83%
See 1 more Smart Citation
“…The aerosol absorption coefficient values obtained at Granada in summer (5-28 Mm −1 ) are similar to those obtained by a MAAP (the same instrument used in this study) during summer 2002 in Vienna (population 1.8 million) which ranged from 8-30 Mm −1 (Hitzenberger et al, 2006). In addition, the mean value of σ ap (21±10 Mm −1 ) observed at Granada is also comparable to the values of σ ap of 22 Mm −1 obtained at the urban costal Toulon, France during (Saha et al, 2008.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbesupporting
confidence: 83%
“…At present, the MAAP is the most reliable filter-based instrument for aerosol absorption coefficient measurements (Petzold and Schönlinner, 2004;Petzold et al, 2005;Sheridan et al, 2005;Hitzenberger et al, 2006). The study of Petzold et al (2005) and Sheridan et al (2005) showed that the absorption coefficients measured by the MAAP are in good agreement with those measured by photoacoustic spectrometry and simultaneous measurement of aerosol extinction and aerosol scattering.…”
Section: Instruments and Measurementsmentioning
confidence: 92%
“…As we have used very long (monthly and seasonal) averages of EBC, such long range averaging have given an advantages of reduction in uncertainties originating from instrumental noise and other sampling conditions like humidity etc. From inter comparison between different techniques; it was found that in spite of site-specific and instrument-specific instantaneous value of EBC, the average concentration obtained by various techniques tend to agree within the instrumental uncertainties for aged (away from strong sources) aerosols (Hitzenberger et al, 2006;Dumka et al, 2010). As there are no such prominent and strong local sources of fresh EBC near to our observational site, the concept of aged aerosol is well applicable to our site also.…”
Section: Instrumentation (Measurement Data)mentioning
confidence: 66%
“…From different literature, it is clear that all the available methods for measurement of EBC mass concentration are based on some assumptions that are instrument specific, site specific and also depends on the type of carbonaceous aerosol, and its fraction to the total aerosol mass (Weingartner et al, 2003;Hitzenberger et al, 2006;Moorthy et al, 2007;Nair et al, 2007). So there is no standard method that gives unique value of EBC concentration for a particular location.…”
Section: Instrumentation (Measurement Data)mentioning
confidence: 99%
“…Holzverbrennung als wichtige Aerosolquelle für primäres und sekundäres organisches Aerosolmaterial in Österreich und Europa Pio et al, 2008;Caseiro et al, 2009) (Leder, 2008 (Feczko et al, 2007). Der Anteil von Ruß liegt am Sonnblick bei etwa 10 % des TC (Hitzenberger et al, 2000a (Hitzenberger et al, 2006b). Im Bereich < 100 nm zeigt sich oft ein zusätzlicher Mode mit mittleren Durchmessern um 0,09 μm durch frische Verkehrsemissionen (Berner et al, 1996).…”
Section: Quellenabhängige Chemische Zusammensetzung Des Aerosolsunclassified